Sistem Informasi Hasil Ulangan Harian Berbasis Web - Indah Puji Djahuari; F.X. Wisnu Yudo Untoro (Informatics Engineering Department-UWKS, 2019)
Data Processing Information Systems Web-Based Daily Value Deuteronomy is a system that provides information reports online activity of students in the form of daily test results report grades and student information concerned with web-based, so it helps speed and quality in the delivery of information. Problems that occur in the processing of value in SMP Negeri 5 Manokwari today is still conventional, as is still done manually or by writing in leger value so much time and effort required to process the task. This study aims to establish an information system which facilitates the checking value, recording and reporting of data values ??computerized student. In addition to the web-based data information can be accessed anytime and anywhere. This system works to enter and store data report student grades. This study has resulted in a processing system that helps value the work of teachers and can help users to perform processing values ??to the management of the value that can be processed effectively and efficiently, so that it can directly access and can be conveyed properly.